2010
DOI: 10.1179/174313209x385554
|View full text |Cite
|
Sign up to set email alerts
|

Decreased cerebral cortex and liver 5-HT2Areceptor gene expression and enhanced ALDH activity in ethanol-treated rats and hepatocyte cultures

Abstract: Our results suggest that the decreased serotonin function mediated through 5-HT(2A) receptors have a regulatory role on ALDH activity. This will have clinical significance to correct alcoholics from addiction due to allergic aldehyde accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Thus, 5-HT may play an important role in addiction [71]. Previous studies have revealed that addictive behavior with alcohol [72] and pathological gambling [73] are associated with lower 5-HT levels. In addition, several studies have reported that light exposure increases blood 5-HT levels in a specific brain region in humans and rats [74][75][76][77].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 5-HT may play an important role in addiction [71]. Previous studies have revealed that addictive behavior with alcohol [72] and pathological gambling [73] are associated with lower 5-HT levels. In addition, several studies have reported that light exposure increases blood 5-HT levels in a specific brain region in humans and rats [74][75][76][77].…”
Section: Discussionmentioning
confidence: 99%
“…This stress treatment also decreases the level of serotonin and its metabolites in frontal cortex and striatum (Ahmad et al, 2010). On top of these effects, repeated binge drinking exacerbates the increase of extracellular glutamate levels while further reducing brain serotonin levels (George et al, 2010; Szumlinski et al, 2007). Antagonizing NMDA receptors and type I metabotropic glutamatergic receptors had been shown to ameliorate the impact on synaptic structure induced by chronic unpredictable stress (Li et al, 2011) and reduce binge intake (Cozzoli et al, 2012; Cozzoli et al, 2014; Lum et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, both studies had small sample sizes, and thus the divergent results might come from their limited power. Future studies of this polymorphism and the presence of the alcohol dependence remain an interesting focus for investigations, especially in light of the recent findings that decreased 5-HT function mediated through 5-HT2A receptors has been reported to elevate aldehyde dehydrogenase (ALDH) activity in the brain stem of alcohol treated rats and in vitro hepatocyte cultures (George et al, 2010). …”
Section: Discussionmentioning
confidence: 99%